The Green Regulatory Tapes and Their Reflections on the Job Development - A Study for the Sample of Employees in the Nineveh Directorate for Bridges & Roads - خليف, سلطان احمد; مجيد, مجيد حميد; يوحنا, جليلة كوركيس (Journal of Economics and Administrative Sciences, 2018)
The performance of job effectively requires narrowing the meaningful routine activities and attempting employing the job procedures in favor of public welfare through adding the green impact as well as removing them from the red tapes which reflect the firmness of procedures, to enable the job parties to make their job independently, and pushing them to gain priority in the competition layer. This is not attaining easily amidst the regulatory problems expressed by the complication of procedures, the thing which make identifying the problem of the study through the following question:Should we make the complex of procedures and their firmness a way to adopt the idea of the green regulatory tapes supporting the situations of development on the level of organization (the sample of the study)?    The study has adopted several aims; the most important one is "showing the participation of the green regulatory tapes indicators in the development process on the level of the researched organization. The study has conducted on the arbitrary sample (50) employees in the directorate of roads and bridges Nineveh. The questionnaire was the main tool in addition to depending on several statistical methods such as (frequency, percentage, standard deviations, means, and variance analysis). The study has reached into several conclusions such as the positiveness of the indicators for the green regulatory tapes supported by job development. Building on those conclusions, the study arrived at some recommendations.